Is hypoglycemia expensive in China?. Issue 5 (5th February 2021) - Lan, Kuixu; Wang, Jian; Nicholas, Stephen; Tang, Qun; Chang, Alison; Xu, Junfang
Abstract: Background: As a common medical emergency in individuals with diabetes, hypoglycemia events can impose significant demands on hospital resources. Based on diabetes patients with and without hypoglycemia, we assess the cost of hypoglycemic events on China's hospital system. Method: Our study sample comprised 7110 diabetes episodes, including 1417 patients with hypoglycemia (297 patients with severe and 1120 with non-severe hypoglycemia) and 5693 diabetes patients without hypoglycemia. Data on patient social-demographics, length of hospital stay, and hospitalization costs were collected on each patient from Health Information System in Shandong province, China. The additional hospital costs caused by hypoglycemia were assessed by the cost difference between diabetes patients with and without hypoglycemia, including severe and non-severe hypoglycemia. China-wide hospital costs of hypoglycemia were estimated based on adjusted additional hospital costs, comprising inspection, treatment, drugs, materials, nursing, general medical costs, and other costs, caused by hypoglycemia, the prevalence of diabetes and hypoglycemia events, and the rates of hospitalization. Multiple sensitivity analyses were conducted to assess the impact of variations in the key input parameters on the primary estimates. Results: Total hospital costs for patients with hypoglycemia (US$3020.61) were significantly higher than that of patients without hypoglycemia (US$1642.91). The average additional cost caused by hypoglycemia was US$1377.70, with higher average costs of US$1875.89 for severe hypoglycemia and lower average costs of US$1244.76 for non-severe hypoglycemia. The additional hospital cost caused by severe and non-severe hypoglycemia patients was higher for the 60 to 75 year old group, married patients and patients accessing free medical services. Generally, hypoglycemic patients with Urban and Rural Resident Basic Medical Insurance incurred higher additional hospital costs than patients with Urban Employees Basic Medical Insurance. Based on these estimates, the total annual additional hospital costs arising from hypoglycemia events in China were estimated to be US$67.52 million. Sensitivity analyses suggested that the costs of hypoglycemia events ranged up to US$49.99 million to 67.52 million. Conclusion: : Hypoglycemic events imposed a substantial cost on China's hospital system, with certain subgroups of patients, such as older patients and those with free health insurance, using medical resources more intensively to treat hypoglycemia events. We recommend more effective planning of prevention and treatment regimes for hypoglycemia patients; further reform to China's health insurance schemes; and better hospital cost control for those accessing free hospital services. Abstract : Supplemental Digital Content is available in the text